Emphysematous cystitis and necrotizing fasciitis - Wang, Peter Z.T.; Martin, Paul Robert; Luke, Patrick P.W. (Canadian Urological Association Journal, 2014)
Emphysematous cystitis is an uncommon and often severe infectious condition of the bladder that usually affects women and diabetics. We report a case of a 62-year-old male patient who presented with concomitant emphysematous cystitis and necrotizing fasciitis of the right leg. The patient was initially managed with emergent disarticulation of the right leg. Tissue cultures were positive for Ciprofloxacin-resistant Klebsiella pneumoniae. He was treated with Piperacillin-Tazobactam; however, due to the failure of conservative management of the condition, the patient underwent a cystoprostatectomy with ileal conduit. To our knowledge, this is the first report of concomitant emphysematous cystitis and necrotizing fasciitis requiring aggressive surgical intervention for both diseases.